Global Research Trends on Oil Palm Plantation and Deforestation: A Bibliometric Analysis - Ramadhan, Edwin Mahatir Muhammad; Suprehatin, Suprehatin (International Journal of Oil Palm, 2025)
Palm oil is one of the most efficient and widely consumed vegetable oils globally, but its expansion has been linked to tropical deforestation, biodiversity loss, and land use change. As global environmental concerns intensify, scholarly interest in the palm oil-deforestation nexus has grown rapidly. This study offers an updated science mapping analysis of global research on this topic until 10 July 2025. Drawing on 1,622 peer-reviewed articles retrieved from Scopus and Web of Science, we applied bibliometric analysis and science mapping to examine publication trends, thematic structures, collaboration networks, and the intellectual foundations of the field. Findings reveal a sharp increase in research output since the early 2000s, with Environmental Research Letters, Land Use Policy, and PLoS One emerging as the most relevant sources. The most prolific authors and institutions are primarily based in Europe, North America, and Southeast Asia, with the University of Göttingen and Bogor Agricultural University (IPB University) playing central roles. Indonesia now leads in single-country publications, reflecting its growing research capacity and strategic importance in the global palm oil landscape. The existing literature is predominantly framed through ecological and technical lenses, focusing on biodiversity, emissions, and sustainability certification. Keyword and co-citation analyses show emerging themes such as ‘spatial analysis’, ‘machine learning’, and expanding regional focus beyond Southeast Asia. However, critical gaps remain, particularly around social justice, land rights, and indigenous knowledge. This study highlights the need for more inclusive and interdisciplinary research approaches that foreground power dynamics, local voices, and alternative knowledge systems. Additionally, as a major producer and increasingly active research contributor, Indonesia holds strong potential to be a focus in future research agendas. The study provides a strategic foundation for researchers, funders, and policymakers engaged in sustainability and land-use governance.